Adsorption of Coxsackievirus in Sediments: Influencing Factors, Kinetics, and Isotherm Modeling - Mengyu Li; Xiaoying Zhang; Weiheng Su; Fangfei Cai; Tianshan Lan; Zhenxue Dai (Applied Sciences, 2024)
Drinking groundwater contamination by pathogenic viruses represents a serious risk to worldwide public health, particularly for enteric viruses, which exhibit high prevalence and occurrence during outbreaks. Understanding how enteric viruses adsorb in groundwater is essential to protecting human health and ensuring the sustainable use of water resources. The adsorption properties of Coxsackievirus A16 (CA16), a common gastrointestinal virus that spreads through groundwater, were investigated in this work. A typical batch equilibrium approach was used to investigate CA16 adsorption and factors that influence it. In a laboratory recognized nationally as a biosafety level 2 facility, stringent research protocols were followed to guarantee compliance with experimental standards. The variables that were investigated included the size of the sediment particles, the starting concentration of the virus, temperature, pH level, and humic acid content. The findings showed that the CA16 virus was more strongly attracted to finer sediment particles and that its adsorption increased as the size of the sediment particle decreased. Furthermore, it was discovered that higher temperatures improved the CA16 virus’s ability to bind to sediment particles. The pH of the aqueous environment has a significant effect on the effectiveness of virus adsorption; higher effectiveness was seen in acidic environments. Furthermore, it was found that the presence of humic acid decreased the ability of clay to adsorb CA16, suggesting that humic acid has a detrimental influence on clay’s ability to adsorb viruses. The examination of kinetic models demonstrated that, in every scenario examined, the adsorption process of CA16 adhered to the pseudo-second-order kinetics model. Additionally, the Langmuir and Freundlich isotherm models were used to assess the equilibrium data that were collected in this investigation. The outcomes amply proved that the most accurate representation of the adsorption equilibrium was given by the Langmuir isotherm model. The study offered a solid scientific foundation for treating groundwater and creating plans to stop the spread of viruses.